Pengaruh Kompetensi, Pengendalian Internal Dan Partisipasi Masyarakat Terhadap Efektivitas Pengelolaan Dana Desa Suru Dawarblandong Mojokerto - Rizaldi, Dimas Fahmi; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to explain the influence of competence, internal control and community participation on the effectiveness of village fund management in Suru Dawarblandong Mojokerto. This research uses quantitative research methods. The data analysis method used is multiple linear regression analysis. Sources of data in this study were primary data using questionnaires and assessed with a Likert scale obtained from Suru Dawarblandong Mojokerto. Village apparatus, totaling 40 people. Sampling was carried out using purposive sampling method. The results of this study indicate that the variables of competence, internal control and community participation have a positive effect on the effectiveness of managing village funds in Suru Dawarblandong Mojokerto. Keywords: Competence, Internal Control, Community Participation, Effectiveness of Village Fund Management